ANALISIS PENERAPAN MEDIA PEMBELAJARAN PREZI TERHADAP HASIL BELAJAR SISWA KELAS X TPHP PADA MATA PELAJARAN PENGENDALIAN MUTU DALAM PROSES PENGOLAHAN DI SMK NEGERI 3 TAKALAR - Febrianto, Febrianto; Rais, Muhammad; Nurmila, Nurmila (Universitas Negeri Makassar, 2016)
This research is a classroom action research, which aimed to improve student learning outcomes on the quality control of processing subject in class X agricultural processing technology expertise SMK Negeri 3 Takalar with the use of teaching media, Prezi. The subjects of this research were the students of class X agricultural processing technology expertise SMK Negeri 3 Takalar in the second semester of academic year 2016/2017 that consist of 29 students. This study was conducted in two cycles consisting of four step: planning, implementation, monitoring/observation and reflection. The collection data activities of students learning outcomes is done by using observation sheet and test sheet at the end of the study in the first cycle and the second cycle. The data were analyzed quantitatively and qualitatively. Based on the results of this study concluded that the use of Prezi can improve the learning outcomes of class X TPHP SMK Negeri 3 Takalar.